2002
DOI: 10.3758/bf03195790
|View full text |Cite
|
Sign up to set email alerts
|

The duration of 3-D form analysis in transformational apparent motion

Abstract: Transformational apparent motion (TAM) occurs when a figure changes discretely from one configuration to another overlapping configuration. Rather than an abrupt shape change, the initial shape is perceived to transform smoothly into the final shape as if animated by a series of intermediate shapes. We find that TAM follows an analysis of form that takes 80-140 msec. Form analysis can function both at and away from equiluminance and can occur over contours defined by uniform regions as well as outlines. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
63
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 136 publications
4
63
0
Order By: Relevance
“…1 When the stimulus changes from the local to the global percept, it appears to move more slowly, even though the dots themselves never change speed at the level of the stimulus. This implies that the perceived speed of the global-motion percept is not determined solely by the local speeds of the individual dots, which is consistent with the view that motion is computed in light of the outputs of a stage of form analysis (Ames, 1951;Caplovitz & Tse, 2007a, 2007bKlopfer, 1991;Lorenceau & Shiffrar, 1992;Shiffrar, Li, & Lorenceau, 1995;Sinha & Poggio, 1996;Tse, 2006;Tse & Logothetis, 2002;Ullman, 1979). In the present article, we describe two psychophysical experiments that further examined the influence of perceived form on perceived motion.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…1 When the stimulus changes from the local to the global percept, it appears to move more slowly, even though the dots themselves never change speed at the level of the stimulus. This implies that the perceived speed of the global-motion percept is not determined solely by the local speeds of the individual dots, which is consistent with the view that motion is computed in light of the outputs of a stage of form analysis (Ames, 1951;Caplovitz & Tse, 2007a, 2007bKlopfer, 1991;Lorenceau & Shiffrar, 1992;Shiffrar, Li, & Lorenceau, 1995;Sinha & Poggio, 1996;Tse, 2006;Tse & Logothetis, 2002;Ullman, 1979). In the present article, we describe two psychophysical experiments that further examined the influence of perceived form on perceived motion.…”
supporting
confidence: 64%
“…The global percept here may be seen to move more slowly because of an increase in speed-discrimination threshold, which is caused by the parsing of the Ls into two large squares in the global be determined solely on the basis of local speed-tuned mechanisms. Rather, motion appears to be computed in light of input from a global analysis that interpolates forms such as the virtual squares that were perceived in the global configuration (Ames, 1951;, 2007a, 2007bKlopfer, 1991;Lorenceau & Shiffrar, 1992;Shiffrar et al, 1995;Sinha & Poggio, 1996;Tse, 2006;Tse & Logothetis, 2002;Ullman, 1979). Instantaneous motion vectors must be computed in light of the outputs of such nonlocal grouping or segmentation operations.…”
Section: Discussionmentioning
confidence: 99%
“…In the small-disparity-gradient condition, the specified motion trajectory was turned away from the center of the observer's face by about 45 cm; however, in the basic and large-disparity conditions, the motion trajectory went through a point about 3 cm to one side of the center of the observer's face. Tse and Logothetis (2002) found that high-level motion processing, which analyzes the 3-D shape and trajectory of motion in depth, needs about 100 msec to generate the apparent motion with consistent direction. In Experiment 4, as well as in the other experiments in this study, the SOA for the two stimuli was at most 64 msec.…”
Section: Discussionmentioning
confidence: 99%
“…The original formulation of this principle goes back to Wertheimer (1912) and is a basic principle of Gestalt theory (Koffka 1935): it was applied to explain mathematically the trajectories of apparent movement (Foster 1979;Farrel 1983;Shepard 1984;Proffitt et al 1988;Tse and Logothetis 2002).…”
mentioning
confidence: 99%